Early development and gas exchange of Ficus adhatodifolia Schott under different levels of shading - Gonçalves, G. G. [UNESP]; Takata, W. H.S. [UNESP]; Ming, L. C. [UNESP]; Campos, R. A. [UNESP]; Ribeiro, E. [UNESP]; Ferreira, M. I. [UNESP] (International Society for Horticultural Science (ISHS), 2016)
Figueira-Branca (Ficus adhatodifolia Schott) is a medicinal species. The latex of this plant, which is used in folk medicine to treat worms, is obtained mainly by extraction from the plant. If the plant is used indiscriminately, the result may be the loss of genetic diversity and chemistry of the species. Thus, studies on early development are important tools that can help ensure greater chances of conservation and maintenance of genetic diversity of the species. The current work, done in Botucatu, São Paulo, Brazil, studied the growth and gas exchange of figueira branca seedlings under different levels of shading. The experimental design was a randomized block in a factorial scheme 4×6 (0, 30, 50 and 70% of shading) and six sampling times (30, 60, 90, 120, 150 and 180 days) in three replicates. The variables evaluated were leaf area, total dry weight, leaf area ratio (LAR), specific leaf area (SLA), absolute growth rate (AGR), net assimilation rate (NAR), relative growth rate (RGR) rate of CO2 assimilation (4), leaf conductance (Gs), transpiration (E), intercellular CO2 concentration (Ci), water use efficiency (WUE), carboxylation efficiency (CE). The biométrie data of plants on growth under 30% of shading showed the higher means (1157.5 dm2 and 7.5398 g). Plant growth was highest in plants subjected to 30% shading until 90 days growth. After this time, the plants under 50 and 70% had the best growth until 180 days. Measurements of gas exchange showed that plants under 30% of shading had the highest photosynthetic rate. Thus, the best environment for early growth towards seedlings production of Ficus adhatodifolia occurs under 30% of shading.
Keywords: Growth analysis; Light; Medicinal plants; Morctcecte; Photosynthesis